Implementasi Pendekatan Saintifik melalui Jari Kreasi Sampah Bocah Cilik di Kawasan Pantai Parangtritis Yogyakarta - Hana Wahyuni; Yora Harlistyarintica; widiyawanti widiyawanti (Universitas Sebelas Maret, 2017)
This activity aims to foster a sense of environmental love early childhood. The target is children around Parangtritis Beach area. The child is aged 4-12 years old which amounts to activities of 30 children. Activities undertaken in the form of waste exploration, outbound, handicraft made from inorganic waste (plastic cups, bottle caps and bottles), garbage creation contest and strengthening the material. The educators of this activitity are the implementer team from Program Kreativitas Mahasiswa Jari Kreasi Sampah Bocah Cilik. The manifestation of the growing love of the environment is shown by the increase of knowledge, skills and attitude. The results of the creation of simple crafts such as glass dolls, bottle caps, spider dolls, and painting bottles. Parents and surrounding communities strongly support this activity.